DNA fingerprinting for crop varietal identification: Fit-for-purpose protocols, their costs and analytical implications - Poets, Ana; Silverstein, Kevin; Pardey, Philip G.; Hearne, Sarah; Stevenson, James R. (CGIAR Standing Panel on Impact Assessment, 2020)
This study provides guidance to agricultural researchers wanting to integrate DNA fingerprinting of crop varieties into their field research. The authors draw on experience from a number of methodological experiments from the past six years, and a technical workshop on DNA fingerprinting methodology convened in 2018. There are many possible methodological variations of DNA fingerprinting, and this guide helps researchers match their data needs to the specific protocols that they can use to meet them. A companion non-technical guidebook for social scientists is currently in preparation.